2007
DOI: 10.5507/bp.2007.016
|View full text |Cite
|
Sign up to set email alerts
|

Relation of blood platelet count during carbamazepine and oxcarbazepine treatment with daily dose, and serum concentrations of carbamazepine, carbamazepine-10, 11-epoxide, and 10-hydroxycarbazepine

Abstract: Background: Carbamazepine (CBZ) occasionally causes haematological disorders such as thrombocytopenia, and recently a case of oxcarbazepine (OXCBZ)-induced thrombocytopenia has been described. The aim of our study was blood platelet count determination in epileptic patients treated with CBZ and OXCBZ, and its relationship with the dose and serum levels of these drugs and its metabolites.Methods: The serum levels of CBZ and its epoxide, and the pharmacologically active monohydroxy derivative of OXCBZ were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Correspondingly, the assessment of 137 patients who were on CBZ therapy and 60 patients on oxcarbazepine (OXCBZ) after 3 months of treatment revealed a negative correlation between platelet count and daily doses of both drugs, and five patients (four received CBZ and one received OXCBZ) had a significant reduction in platelets (thrombocytopenia) with increased platelets destruction and reduced platelet survival. 19 In the current study, CBZ therapy and its duration were associated with reduced white blood cells (WBCs), within the neutral range, in epileptic children. Also, leukopenia was reported in 31.7% (13 out of 41) of epileptic Iranian children and adolescents on CBZ therapy after 1 year follow-up, with one patient having to discontinue treatment due to severe leukopenia after 6 months.…”
Section: Discussionmentioning
confidence: 73%
“…Correspondingly, the assessment of 137 patients who were on CBZ therapy and 60 patients on oxcarbazepine (OXCBZ) after 3 months of treatment revealed a negative correlation between platelet count and daily doses of both drugs, and five patients (four received CBZ and one received OXCBZ) had a significant reduction in platelets (thrombocytopenia) with increased platelets destruction and reduced platelet survival. 19 In the current study, CBZ therapy and its duration were associated with reduced white blood cells (WBCs), within the neutral range, in epileptic children. Also, leukopenia was reported in 31.7% (13 out of 41) of epileptic Iranian children and adolescents on CBZ therapy after 1 year follow-up, with one patient having to discontinue treatment due to severe leukopenia after 6 months.…”
Section: Discussionmentioning
confidence: 73%
“…[8,9] Thrombocytopenia observed in some patients using CBZ or OXC has been attributed to excessive destruction of peripheral blood platelets. [10] It has been shown that the mechanism of thrombocytopenia is not directly related to the toxicity of CBZ, OXC or their metabolites. [10] Routine monitoring of platelet counts is recommended in patients treated with CBZ and OXC.…”
Section: Discussionmentioning
confidence: 99%
“…[10] It has been shown that the mechanism of thrombocytopenia is not directly related to the toxicity of CBZ, OXC or their metabolites. [10] Routine monitoring of platelet counts is recommended in patients treated with CBZ and OXC. [10] VPA may cause cytopenia by directly affecting the bone marrow or acting on one or more cell lines (pancytopenia, neutropenia, leukopenia).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it was suggested that oxcarbazepine causes thrombocytopenia and thrombocytopenia that regress with the cessation of treatment, and these patients should be monitored concerning hemogram parameters [19,20] . Hyperhomocysteinemia is known to induce atherosclerosis through endothelial damage.…”
Section: Discussionmentioning
confidence: 99%